Designing an Accelerated Graduate Evaluation Course Using the First Principles of Instruction and Interactive Media. (June 2020) - Gardner, Joel; Barclay, Matt; Kong, Younghee; LeVally, Carolyn
Evaluation skills are complex and require careful design to teach effectively. In our master's program in Instructional Design and Performance Technology, students experienced unnecessary difficulty in our evaluation course. To facilitate students' success, we redesigned the course using interactive media and the first principles of instruction, a comprehensive, research-based approach to creating quality teaching and learning. This article describes the obstacles identified in the initial evaluation course and how we worked to reduce their impact using interactive media and the first principles of instruction in the course redesign. We share course redesign results and make recommendations for designing evaluation courses.